2022
DOI: 10.1039/d2nj03499a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and computationally assisted spectroscopic study of tautomerism in 3-(phenyl(2-arylhydrazineylidene)methyl)quinoxalin-2(1H)-ones

Abstract: The recently developed efficient protocol combining implicit and explicit, accurate quantum mechanical modeling of the condensed state [Katsyuba et al., J. Chem. Phys. 155, 024507 (2021)] is used to describe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…In other words, we demonstrated that the vibrational modes and derivatives of the polarizability of a solute are mainly locally influenced by its immediate environment, while the effect of bulk water is rather modest. This is in parallel with the outcome of our liquid-state IR spectra simulations, 6,[8][9][10][11][12] which showed that the dipole moment derivatives of a solute are mainly locally influenced by its immediate surroundings. This knowledge not only improves our understanding of solute-solvent interactions, but also allows minimization of the computational costs of QM simulations of the liquid-state Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In other words, we demonstrated that the vibrational modes and derivatives of the polarizability of a solute are mainly locally influenced by its immediate environment, while the effect of bulk water is rather modest. This is in parallel with the outcome of our liquid-state IR spectra simulations, 6,[8][9][10][11][12] which showed that the dipole moment derivatives of a solute are mainly locally influenced by its immediate surroundings. This knowledge not only improves our understanding of solute-solvent interactions, but also allows minimization of the computational costs of QM simulations of the liquid-state Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
“…Initially 6 we calculated the IR spectrum of any system, modeled within the framework of our cluster approach, as a thermodynamic average of the individual spectra computed for each complete cluster at the DFT level. Nevertheless, further studies [8][9][10][11][12] have shown that the difference between the spectrum of the lowest-energy cluster and that averaged from all clusters in the final ensemble is negligible, and hence the averaging was avoided to minimize computational expenses. The same turned out to be true for the present case, which is clearly seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Conformer-Rotamer Ensemble Sampling Tool (CREST) 15 software developed by Grimme et al has gained much attention because of its practicability. CREST invokes another software, Extended Tight Binding (xTB), 16 which supports the novel semiempirical method GFNn-xTB (n = 0, 1, 2), to achieve rapid and relatively accurate computation in conformational search and sampling, [17][18][19] entropy and heat capacity calculation, 20 protonation/deprotonation sites, 21 and tautomerism screening 22 and is suitable for explaining the experimental data using theory principles.…”
Section: Introductionmentioning
confidence: 99%